Tinjauan Yuridis Terhadap Pelaku Tindak Pidana Perdagangan Manusia (Human Trafickking) - Cindy Regita Pratiwi; Mahzaniar (Inovasi Pratama Internasional. Ltd, 2022)
Trafficking in persons is a symbol/social status where people who have high social status (economic and political power) are ensured to have slaves. Everyone who has slaves will be considered to have a high social status, so it has become a common thing for people who have a high social status. In this problem, the researcher asserts that the legal questions and objectives for human trafficking are as follows: 1. How is the application of the legal system governing the occurrence of the crime of human trafficking (human trafficking) 2. How is the analysis of judge decisions in trafficking decisions Human Trafficking at Number.801/Pid.Sus/2020/PN Lbp. 3. What are the obstacles faced by law enforcement officers in tackling the crime of trafficking in persons (human trafficking). Research is the most important part of the whole series of activities for writing a scientific paper, because to answer the main research problems, the object of the problem described in the formulation of the problem will be answered. The research location is a place or area where the research will be carried out. The location of this research is located at the Lubuk Pakam State Court Class I-A Jl. General Sudirman No. 58 Lubuk Pakam, Postal Code: 20512, Tel/Fax: (061) 7955861, North Sumatra. In the application of the legal system that regulates the occurrence of the criminal act of trafficking in persons, it has been very widespread which has been organized both on a national and international scale. So that makes the government feel difficult in tackling the crime of trafficking in persons.